2014
DOI: 10.1095/biolreprod.113.108845
|View full text |Cite
|
Sign up to set email alerts
|

The Aryl Hydrocarbon Receptor Is Important for Proper Seminiferous Tubule Architecture and Sperm Development in Mice1

Abstract: The aryl hydrocarbon receptor (AHR) is known for its roles in xenobiotic metabolism and essential physiologic processes such as cell growth, death, and differentiation. AHR is also an important regulator of male reproductive processes. However, no studies have characterized the consequences of loss of AHR in spermatogenesis. We used Ahr knockout (Ahr(-/-)) mice to assess the effects of loss of AHR on the architecture and gene expression of the seminiferous epithelium and functional sperm outcomes. The histopat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
30
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 41 publications
7
30
0
Order By: Relevance
“…The overall success rate for control mating pairs was 95% ( Table 1 ) and control males in our study exhibited normal sperm numbers ( Figure 2 ) with the percent of morphologically normal sperm within the range reported by others for adult C57bl/6 mice [39], [40] ( Figure 3 ). Regardless of exposure (or lack of exposure), tail defects were the most common morphological abnormality.…”
Section: Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…The overall success rate for control mating pairs was 95% ( Table 1 ) and control males in our study exhibited normal sperm numbers ( Figure 2 ) with the percent of morphologically normal sperm within the range reported by others for adult C57bl/6 mice [39], [40] ( Figure 3 ). Regardless of exposure (or lack of exposure), tail defects were the most common morphological abnormality.…”
Section: Resultssupporting
confidence: 85%
“…We therefore subjected caudal sperm smears to immunolocalization of the AhR. In agreement with data described by Hansen et al [40], sperm from control animals exhibited minimal AhR expression, which was localized to the acrosome and mid-piece ( Figure 4A ). However, sperm obtained from mice with a direct (F1-F2) or indirect (F3) TCDD exposure history had significantly (p≤0.001) increased immunolocalization of AhR compared to control cells ( Figure 4B–D ).…”
Section: Resultssupporting
confidence: 76%
See 1 more Smart Citation
“…Further experiments illustrated that depletion of AhR induced germ cell apoptosis. This result is similar to the finding from another report, which used a different strategy to knock out AhR in mice (22). Along with infertility in this study, we found ductal growth in the mammary fat pad of male AhR −/− mice.…”
Section: Discussionsupporting
confidence: 92%
“…We were unable to evaluate a direct role for AHR in mammalian healthspan because Ahr −/− mice lack ILC3s (40), which themselves may mediate indole effects in aged mice. Notably, Ahr −/− mice also exhibit diminished reproductive capacity, which is at least in part due to deficiencies in sperm production, motility, and sensitivity to oxidative stress (41). Although, indole and ICA bind AHR and activate AHR-dependent transcriptional responses (23), AHR-independent mechanisms may also mediate effects of indole or its derivatives.…”
Section: Discussionmentioning
confidence: 99%